PREDIKSI PENGHASILAN PERUSAHAAN BUS TRANSWISATA MENGGUNAKAN METODE LEAST SQUARE - Akbar, Alfin Nuril Fathil; Rakhma Devi, Putri Aisyiyah (Antivirus : Jurnal Ilmiah Teknik Informatika, 2022)
Tourism is one of the fields in Indonesia that is engaged in serving foreign tourists and domestic tourists who visit tourist objects in Indonesia. Transwisata is a private company engaged in tourism in the city of Surabaya, East Java. Transwisata provides buses for personal use, buses for tourism, and buses for other tourism, besides that in Transwisata there are also travel cars which are usually used for travel for tourists who want to travel to East Java and outside East Java. Knowing the income to be earned in the next period is still based on recording income on previous income, causing an inaccurate prediction. The Least Square method can be used to Forecast on a sale, because this method is one of the techniques in the preparation of a sales Forecast by minimizing the value of the criterion function of the number of squares of errors in the prediction. The least squares method has an error value to determine the method, namely the value of Mean Squad Error (MSE), Mean Absolute Deviation (MAD) and Mean Absolute Percentage Error (MAPE). In this study, it was found that the Least Square method was very well used in the results of bus transtourism income and got an evaluation value of forecasting accuracy with a MAD value of 495770.466, an MSE value of 2.9494 and a MAPE value of 0.2622%. .